Ultrahigh-density PIN-PYN-PT solid solution piezoelectric ceramic and preparation method thereof

By preparing PIN-PYN-PT solid solution piezoelectric ceramics with the chemical formula xPb(In0.5Nb0.5)-yPb(Yb0.5Nb0.5)-zPbTiO3, the problem of degradation of existing ceramics at high temperatures is solved, and the performance of existing ceramics is realized. It combines high phase transition temperature and high voltage electrical performance, and is suitable for high-end devices.

CN119219398AActive Publication Date: 2024-12-31XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411370393.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The performance of existing piezoelectric ceramic materials has deteriorated at high temperatures and cannot meet the needs of the high-end device market. Materials with high phase transition temperature and high voltage electrical properties are difficult to develop.

Method used

PIN-PYN-PT solid solution piezoelectric ceramic with the chemical formula xPb(In0.5Nb0.5)-yPb(Yb0.5Nb0.5)-zPbTiO3 is adopted, and the mixture isostatic sintering and DC high-pressure pole isostatic Prepare it by chemical and other steps to improve the density and electrical properties of the ceramic.

Benefits of technology

The high phase transition temperature, superior temperature stability and high voltage electrical performance of ceramics are achieved, the dielectric coefficient of room temperature reaches 3100, and the longitudinal coupling coefficient k33 can reach 0.57. It is suitable for devices such as B-ultrasound probes and ultrasonic transducers, and in Maintain high performance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005067427700000011
    Figure HDA0005067427700000011
  • Figure HDA0005067427700000012
    Figure HDA0005067427700000012
  • Figure HDA0005067427700000021
    Figure HDA0005067427700000021
Patent Text Reader

Abstract

The invention discloses ultrahigh-density PIN-PYN-PT solid solution piezoelectric ceramic and a preparation method thereof, the chemical formula of the adopted piezoelectric ceramic material is xPb (In0. 5Nb0. 5)-yPb (Yb0. 5Nb0. 5)-zPbTiO3, wherein x is more than or equal to 0.05 and less than or equal to 0.5, y is more than or equal to 0.2 and less than or equal to 0.8, and z is more than or equal to 0.05 and less than or equal to 0.5; the preparation process mainly comprises the following steps: synthesizing a precursor, ball-milling and mixing, adding a PVA adhesive solution into dried PIN-PYN-PT ceramic powder, fully mixing and drying to obtain dried powder, carrying out compression molding on the dried powder, carrying out degumming, sintering the obtained ceramic biscuit for 1-3 hours under the conditions of 900-1000 DEG C and 20-100 MPa by adopting hot isostatic pressing, and thus obtaining the PIN-PYN-PT ceramic material. The PIN-PYN-PT piezoelectric ceramic subjected to hot isostatic pressing sintering is obtained; the obtained ceramic is subjected to heat preservation for 0.5-2 h in the oxygen atmosphere of 800-1000 DEG C, annealing and ceramic polarization are conducted, and the ultrahigh-density PIN-PYN-PT solid solution piezoelectric ceramic is obtained and has the high piezoelectric property and dielectric property and meanwhile has the high phase change temperature, the quasi-static piezoelectric constant d33 reaches 620 pC / N, the normal-temperature dielectric coefficient reaches 3100, the Curie temperature TC reaches 350 DEG C, the phase change temperature Trt reaches 230 DEG C, the longitudinal coupling coefficient k33 reaches 0.57, and the ultrahigh-density PIN-PYN-PT solid solution piezoelectric ceramic can be used for preparing the high-density PIN-PYN-PT solid solution piezoelectric ceramic. And the thickness mechanical coupling coefficient kt reaches 0.57.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of piezoelectric ceramic materials, and in particular relates to an ultra-high-density PIN-PYN-PT solid solution piezoelectric ceramic and a preparation method thereof. Background Art

[0002] High-performance piezoelectric ceramics have excellent properties such as high piezoelectricity and high electromechanical coupling coefficient, which bring historic development opportunities to the fields of broadband, high-resolution, high-sensitivity medical ultrasound imaging and underwater acoustic detection, and have great demand in national health, social economy and national security. At present, 90% of the high-performance ceramic materials used in ceramic piezoelectric probes at home and abroad are ceramics from CTS of the United States, and another 10% are ceramics from TRS of the United States. At present, my country's high-performance medical B-ultrasound probe piezoelectric materials are 100% imported, and it is of great significance to further independently develop and produce domestic high-performance piezoelectric ceramics.

[0003] The manufacturing and use process of piezoelectric devices such as B-ultrasound probes, underwater acoustic detection and ultrasonic transducers includes many high-temperature links, which puts high requirements on the use temperature of piezoelectric materials, that is, the ceramic materials used are required to have a high phase transition temperature. In order to ensure the accuracy of the instrument, piezoelectric ceramics must also have high and stable piezoelectric and dielectric properties. At present, mainstream commercial piezoelectric ceramics, such as PMN-PT and PZT5A ceramics, have high piezoelectric properties, but their low phase transition temperature causes their performance to degrade significantly when working at high temperatures; while ceramics represented by PZT8 have a high phase transition temperature, but the piezoelectric performance is low (<300pC / N), which cannot meet the needs of the high-end device market. Therefore, the development of piezoelectric ceramic materials with both high phase transition temperature and high piezoelectricity has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a PIN-PYN-PT piezoelectric ceramic with a high phase transition temperature and a preparation method thereof. The chemical formula of the piezoelectric ceramic material is: xPb(In 0.5 Nb 0.5 )-yPb(Yb 0.5 Nb 0.5 )-zPbTiO3, where 0.05≤x≤0.5, 0.2≤y≤0.8, 0.05≤z≤0.5.

[0005] In order to achieve the above object, on the one hand, the present invention provides an ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic, characterized in that the chemical formula of the PIN-PYN-PT solid solution piezoelectric ceramic used is: xPb(In 0.5 Nb 0.5 )-yPb(Yb 0.5 Nb0.5 )-zPbTiO3, where 0.05≤x≤0.5, 0.2≤y≤0.8, 0.05≤z≤0.5.

[0006] On the other hand, the present invention provides a method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic as described above, comprising the following steps:

[0007] PbO, TiO2, precursor InNbO4 powder, and precursor YbNbO4 powder are weighed according to the stoichiometric ratio, wet ball milled and mixed, and directly dried to obtain a mixed material;

[0008] The obtained mixed material is pre-calcined at 800-1000° C., the pre-calcined product is mixed with ethanol, subjected to secondary dispersion ball milling, and dried and sieved to obtain dry PIN-PYN-PT ceramic powder;

[0009] Add PVA binder solution to dry PIN-PYN-PT ceramic powder, mix thoroughly and dry to obtain dry powder, press the dry powder into a mold, and heat at 600-700°C for 1-4 hours to remove binder to obtain a ceramic green body;

[0010] The obtained ceramic green body is sintered by hot isostatic pressing in an oxygen atmosphere at 900-1000° C. and 20 MPa-100 MPa for 1-3 hours to obtain hot isostatically pressed PIN-PYN-PT piezoelectric ceramics;

[0011] The obtained sample is annealed at 800°C-1000°C for 0.5-2h to obtain ultra-high density PIN-PYN-PT ceramics;

[0012] The ultra-high density PIN-PYN-PT ceramics were coated with silver electrodes on both sides and then subjected to DC high voltage polarization to obtain PIN-PYN-PT solid solution piezoelectric ceramics.

[0013] Further, the preparation of the precursor InNbO4 powder includes: weighing analytically pure In2O3 and Nb2O5 according to the stoichiometric ratio, mixing by wet ball milling, directly drying, and sintering in a high temperature furnace at 900-1100° C. for 2-6 hours to obtain the precursor InNbO4 powder;

[0014] The preparation of precursor YbNbO4 powder includes: weighing analytically pure Yb2O3 and Nb2O5 according to the stoichiometric ratio, mixing by wet ball milling, directly drying, and sintering at 950-1050° C. in a high-temperature furnace for 3-8 hours to obtain precursor YbNbO4 powder.

[0015] Furthermore, the amount of PVA adhesive added is 2wt%-10wt%, and the PVA adhesive is a 10% PVA adhesive solution plasticized with glycerin.

[0016] Furthermore, the oxygen atmosphere during hot isostatic pressing sintering is formed by a mixture of high-purity argon and oxygen.

[0017] Furthermore, the purity of PbO and TiO2 is analytically pure.

[0018] Furthermore, during DC high voltage polarization: the polarization temperature is 120°C, a 30 kV / cm polarization electric field is applied, and the polarization treatment is performed for 30 minutes.

[0019] Furthermore, the obtained PIN-PYN-PT solid solution piezoelectric ceramics have a theoretical density of up to 99.9% and a quasi-static piezoelectric constant d 33 The highest is 620pC / N, the highest dielectric constant at room temperature is 3100, and the Curie temperature T C The highest temperature is 350℃, the phase transition temperature T rt The maximum is 230℃, the longitudinal coupling coefficient k 33 The highest is 0.57, k t The highest is 0.57.

[0020] The present invention also provides a transducer piezoelectric device, which is a PIN-PYN-PT solid solution piezoelectric ceramic prepared by the above method.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] The ternary PIN-PYN-PT piezoelectric ceramic material disclosed in the present invention has excellent temperature stability and high piezoelectric and dielectric properties. Its quasi-static piezoelectric constant d 33 It can reach 620pC / N, the dielectric constant at room temperature can reach 3100, and the Curie temperature T C Up to 350℃, phase transition temperature T rt Up to 230℃, longitudinal coupling coefficient k 33 Up to 0.57, k t It can reach 0.57, and can be used in B-ultrasound probes, ultrasonic transducers and other piezoelectric devices, and maintain high piezoelectric properties at high temperatures. The ceramics prepared by hot isostatic pressing sintering in the present invention have significantly superior density and electrical properties, and sintering in an oxygen atmosphere can reduce oxygen vacancy defects in PIN-PYN-PT piezoelectric ceramics and improve the density of the ceramics.

[0023] In addition, the invention compares the purchased precursors InNbO4, YbNbO4 and the homemade precursors through experiments, and clearly shows that the homemade precursors have better experimental effects, and obtain ceramic materials with significantly higher purity and significantly superior electrical properties. The invention determines the quasi-modular phase boundary (MPB) ratio of the ternary ultra-high density PIN-PYN-PT piezoelectric ceramics through a series of experiments, and obtains the best performance ratio. The preparation method of the invention has the advantages of simple operation, short cycle, low cost and easy large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the X-ray diffraction spectrum of the PIN-PYN-PT piezoelectric ceramic of Example 1 of the present invention;

[0025] Figure 2 This is a surface scanning electron microscope image of the PIN-PYN-PT piezoelectric ceramic of Example 1 of the present invention;

[0026] Figure 3 This is a dielectric temperature spectrum of the PIN-PYN-PT piezoelectric ceramic material of the second embodiment of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the examples of the present invention, and the content of the present invention includes the contents of all the embodiments, but is not limited to the scope. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field who simply replace or modify the contents of the present invention without making creative work are within the scope of protection of the present invention.

[0028] Example 1: An ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic is prepared by the following steps:

[0029] (1) In2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being In2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and directly dried, and then sintered in a high temperature furnace at 900° C. for 2 hours to obtain a precursor InNbO4 powder;

[0030] (2) Yb2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being Yb2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and directly dried, and then sintered in a high temperature furnace at 950° C. for 3 hours to obtain a precursor YbNbO4 powder;

[0031] (3) PbO, TiO2, InNbO4 and YbNbO4 were weighed in sequence according to the stoichiometric ratio. The purity of the raw materials was PbO ≥ 99.9%, TiO2 ≥ 99.9%, InNbO4 ≥ 99.9%, and YbNbO4 ≥ 99.9%, respectively. The specific ratios were: PbO 30.1242 g, TiO2 1.6007 g, InNbO4 0.9076 g, and YbNbO4 17.6351 g. The weighed raw materials were placed in a ball mill, wherein the mass ratio of the raw materials, anhydrous ethanol, and zirconium balls was approximately 1:0.8:6. Zirconia balls with a diameter of 3-10 mm were selected, and the ball milling was performed for 12-24 h. The ceramic slurry was dried in an oven to obtain a dry powder. The dry powder was placed in a crucible and kept at 800° C. for 2 h to obtain a ceramic powder.

[0032] (4) mixing the PIN-PYN-PT ceramic powder in step (3) with anhydrous ethanol for secondary dispersion grinding, the grinding method is ball milling for 12 hours to obtain a ceramic slurry;

[0033] (5) directly drying the PIN-PYN-PT ceramic slurry in step (4) to obtain a dry powder with uniform composition;

[0034] (6) The dried PIN-PYN-PT ceramic powder in step (5) is passed through a 60-mesh sieve, and then a 10% PVA adhesive solution plasticized with glycerol is added, wherein the ratio of PVA to water is 1:9, and the mixture is fully mixed in a mixer to form a viscous premixed material, wherein the amount of PVA adhesive added is 2 wt%;

[0035] (7) directly drying the premixed material in step (6) to obtain a dry powder with uniform composition;

[0036] (8) The dried PIN-PYN-PT ceramic powder in step (7) is passed through 80-mesh and 100-mesh sieves, and the dried ceramic powder between 80-mesh and 100-mesh is taken out, and the obtained ceramic powder is subjected to mechanical uniaxial pressing and heated at 600° C. for 1 hour to debind, thereby obtaining a ceramic green body;

[0037] (9) placing the obtained ceramic green body in a crucible and sintering it by hot isostatic pressing in an oxygen atmosphere composed of oxygen and argon at 900° C. and 20 MPa for 1-3 hours to obtain a hot isostatically pressed sintered PIN-PYN-PT piezoelectric ceramic;

[0038] (10) The obtained sample was annealed at 800°C for 0.5 h to obtain a ceramic sheet of a certain shape, with a ceramic grain size of 5-10 μm and a theoretical density of 99.9%;

[0039] (11) surface grinding the PIN-PYN-PT piezoelectric ceramic obtained in step (10) to obtain a ceramic sheet having roughness, flatness and thickness that meet the requirements;

[0040] (12) Covering both sides of the PIN-PYN-PT piezoelectric ceramic obtained in step (11) with silver electrodes, heating to 120° C., applying a 30 kV / cm polarizing electric field, and performing high temperature polarization for 30 minutes;

[0041] like Figure 1 As shown in FIG. 1 , the PIN-PYN-PT piezoelectric ceramic material of the present invention is a pure perovskite structure. The morphology of the PIN-PYN-PT piezoelectric ceramic grains prepared by the present invention is analyzed by field emission scanning electron microscopy. Figure 2 As shown, the prepared PIN-PYN-PT piezoelectric ceramics have ultra-high density and the ceramic grain size is about 5-10μm.

[0042] Example 2: An ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic is prepared by the following steps:

[0043] (1) In2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being In2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and directly dried, and then sintered in a high-temperature furnace at 950° C. for 2 hours to obtain a precursor InNbO4 powder;

[0044] (2) Yb2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being Yb2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and directly dried, and then sintered in a high temperature furnace at 1000° C. for 6 hours to obtain a precursor YbNbO4 powder;

[0045] (3) PbO, TiO2, InNbO4 and YbNbO4 were weighed in sequence according to the stoichiometric ratio. The purity of the raw materials was PbO ≥ 99.9%, TiO2 ≥ 99.9%, InNbO4 ≥ 99.9%, and YbNbO4 ≥ 99.9%, respectively. The specific ratios were: PbO 30.5128 g, TiO2 0.5404 g, InNbO4 9.1935 g, and YbNbO4 10.0477 g. The weighed raw materials were placed in a ball mill, wherein the mass ratio of the raw materials, anhydrous ethanol, and zirconium balls was approximately 1:0.8:6. Zirconia balls with a diameter of 3-10 mm were selected, and the ball milling was performed for 12-24 h. The ceramic slurry was dried in an oven to obtain a dry powder. The dry powder was placed in a crucible and kept at 850° C. for 2 h to obtain a ceramic powder.

[0046] (4) mixing the PIN-PYN-PT ceramic powder in step (3) with anhydrous ethanol for secondary dispersion grinding, the grinding method is ball milling for 16 hours to obtain a ceramic slurry;

[0047] (5) directly drying the PIN-PYN-PT ceramic slurry in step (4) to obtain a dry powder with uniform composition;

[0048] (6) The dried PIN-PYN-PT ceramic powder in step (5) is passed through a 60-mesh sieve, and then a 10% PVA adhesive solution plasticized with glycerol is added, wherein the ratio of PVA to water is 1:9, and the mixture is fully mixed in a mixer to form a premixed material with a certain viscosity, wherein the amount of PVA adhesive added is 5 wt%;

[0049] (7) directly drying the premixed material in step (6) to obtain a dry powder with uniform composition;

[0050] (8) The dried PIN-PYN-PT ceramic powder in step (7) is sieved through 80-mesh and 100-mesh sieves, and the dried ceramic powder between 80-mesh and 100-mesh is taken out, and the obtained ceramic powder is pressed into shape by a combination of mechanical uniaxial pressing and cold isostatic pressing, and the mixture is kept at 650° C. for 2 h for debinding to obtain a ceramic green body;

[0051] (9) placing the obtained ceramic green body in a crucible and sintering it by hot isostatic pressing, sintering it in an oxygen atmosphere composed of oxygen and argon at 950° C. and 40 MPa for 1.5 hours to obtain a hot isostatically pressed sintered PIN-PYN-PT piezoelectric ceramic;

[0052] (10) annealing the obtained sample at 850° C. for 1 h to obtain the high-performance PIN-PYN-PT piezoelectric ceramic;

[0053] (11) surface grinding the PIN-PYN-PT piezoelectric ceramic obtained in step (10) to obtain a ceramic sheet having roughness, flatness and thickness that meet the requirements;

[0054] (12) Covering both sides of the PIN-PYN-PT piezoelectric ceramic obtained in step (11) with silver electrodes, heating to 120° C., applying a 30 kV / cm polarizing electric field, and performing high temperature polarization for 30 minutes;

[0055] Example 3: An ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic is prepared by the following steps:

[0056] (1) In2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being In2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and mixed, directly dried, and sintered in a high temperature furnace at 1100° C. for 6 hours to obtain a precursor InNbO4 powder;

[0057] (2) Yb2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being Yb2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and directly dried, and then sintered in a high temperature furnace at 1050° C. for 8 hours to obtain a precursor YbNbO4 powder;

[0058] (3) PbO, TiO2, InNbO4, and YbNbO4 were weighed in sequence according to the stoichiometric ratio. The purity of the raw materials was PbO ≥ 99.9%, TiO2 ≥ 99.9%, InNbO4 ≥ 99.9%, and YbNbO4 ≥ 99.9%, respectively. The specific ratios were: PbO 33.3712 g, TiO2 5.9109 g, InNbO4 6.0328 g, and YbNbO4 4.8839 g. The weighed raw materials were placed in a ball mill, wherein the mass ratio of the raw materials, anhydrous ethanol, and zirconium balls was approximately 1:0.8:6. Zirconia balls with a diameter of 3-10 mm were selected, and the ball milling was performed for 16 h. The ceramic slurry was dried in an oven to obtain a dry powder. The dry powder was placed in a crucible and kept at 1000° C. for 2 h to obtain a ceramic powder.

[0059] (4) mixing the PIN-PYN-PT ceramic powder in step (3) with anhydrous ethanol for secondary dispersion grinding, the grinding method is ball milling for 16 hours to obtain a ceramic slurry;

[0060] (5) directly drying the PIN-PYN-PT ceramic slurry in step (4) to obtain a dry powder with uniform composition;

[0061] (6) The dried PIN-PYN-PT ceramic powder in step (5) is passed through an 80-mesh sieve, and then a 10% PVA adhesive solution plasticized with glycerol is added, wherein the concentration of 10% is a ratio of PVA to water of 1:9, and the mixture is fully mixed in a mixer to form a premixed material with a certain viscosity, wherein the amount of PVA adhesive added is 10 wt%;

[0062] (7) directly drying the premixed material in step (6) to obtain a dry powder with uniform composition;

[0063] (8) The dried PIN-PYN-PT ceramic powder in step (7) is passed through 100-mesh and 120-mesh sieves, and the dried ceramic powder between 100-mesh and 120-mesh is taken out, and the obtained ceramic powder is pressed by cold isostatic pressing, and the mixture is heated at 680° C. for 3 h for debinding to obtain a ceramic green body;

[0064] (9) hot isostatic pressing the obtained ceramic green body for 2 hours in an oxygen atmosphere composed of oxygen and argon at 980° C. and 60 MPa to obtain hot isostatically pressed PIN-PYN-PT piezoelectric ceramics;

[0065] (10) annealing the obtained sample at 950° C. for 1.5 h to obtain the high-performance PIN-PYN-PT piezoelectric ceramic;

[0066] (11) surface grinding the PIN-PYN-PT piezoelectric ceramic obtained in step (10) to obtain a ceramic sheet having roughness, flatness and thickness that meet the requirements;

[0067] (12) Cover the PIN-PYN-PT piezoelectric ceramic obtained in step (11) with silver electrodes on both sides, heat it to 120°C, apply a 30 kV / cm polarizing electric field, and perform high-temperature polarization for 30 minutes.

[0068] Example 4: An ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic is prepared by the following steps:

[0069] (1) In2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being In2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and mixed, directly dried, and sintered in a high temperature furnace at 1100° C. for 4 hours to obtain a precursor InNbO4 powder;

[0070] (2) Yb2O3 and Nb2O5 were weighed in accordance with the stoichiometric ratio, with the purity of the raw materials being Yb2O3 ≥ 99.9% and Nb2O5 ≥ 99.9%, respectively, and wet ball milled and directly dried, and then sintered in a high temperature furnace at 1000° C. for 5 hours to obtain a precursor YbNbO4 powder;

[0071] (3) PbO, TiO2, InNbO4, and YbNbO4 were weighed in sequence according to the stoichiometric ratio. The purity of the raw materials was PbO ≥ 99.9%, TiO2 ≥ 99.9%, InNbO4 ≥ 99.9%, and YbNbO4 ≥ 99.9%, respectively. The specific ratios were: PbO 33.3712 g, TiO2 5.9109 g, InNbO4 6.0328 g, and YbNbO4 4.8839 g. The weighed raw materials were placed in a ball mill, wherein the weight ratio of the raw materials, anhydrous ethanol, and zirconium balls was approximately 1:0.8:6. Zirconia balls with a diameter of 3-10 mm were selected, and the ball milling was performed for 16 h. The ceramic slurry was dried in an oven to obtain a dry powder. The dry powder was placed in a crucible and kept at 950° C. for 2 h to obtain a ceramic powder.

[0072] (4) mixing the PIN-PYN-PT ceramic powder in step (3) with anhydrous ethanol for secondary dispersion grinding, the grinding method is ball milling for 24 hours to obtain a ceramic slurry;

[0073] (5) directly drying the PIN-PYN-PT ceramic slurry in step (4) to obtain a dry powder with uniform composition;

[0074] (6) The dried PIN-PYN-PT ceramic powder in step (5) is passed through an 80-mesh sieve, and then a 10% PVA adhesive solution plasticized with glycerol is added, wherein the concentration of 10% is a ratio of PVA to water of 1:9, and the mixture is fully mixed in a mixer to form a premixed material with a certain viscosity, wherein the amount of PVA adhesive added is 10 wt%;

[0075] (7) directly drying the premixed material in step (6) to obtain a dry powder with uniform composition;

[0076] (8) The dried PIN-PYN-PT ceramic powder in step (7) is passed through 100 mesh and 120 mesh sieves, and the dried ceramic powder between 100 mesh and 120 mesh is taken, and the obtained ceramic powder is pressed by cold isostatic pressing, and the mixture is kept at 700° C. for 4 hours for debinding to obtain a ceramic green body;

[0077] (9) placing the obtained ceramic green body in a crucible and sintering it by hot isostatic pressing in an oxygen atmosphere composed of oxygen and argon at 1000° C. and 100 MPa for 3 hours to obtain a hot isostatically pressed sintered PIN-PYN-PT piezoelectric ceramic;

[0078] (10) annealing the obtained sample at 1000° C. for 2 h to obtain the high-performance PIN-PYN-PT piezoelectric ceramic;

[0079] (11) surface grinding the PIN-PYN-PT piezoelectric ceramic obtained in step (10) to obtain a ceramic sheet having roughness, flatness and thickness that meet the requirements;

[0080] (12) Cover the PIN-PYN-PT piezoelectric ceramic obtained in step (11) with silver electrodes on both sides, heat it to 120°C, apply a 30 kV / cm polarizing electric field, and perform high-temperature polarization for 30 minutes.

[0081] The present invention performs hot isostatic pressing sintering in an atmosphere of high-purity argon-oxygen mixed gas. Hot isostatic pressing sintering (also known as high-temperature isostatic pressing sintering, Hot Isostatic Pressing Sintering, abbreviated as HIP) refers to subjecting the sample to isostatic pressure in all directions during the sintering process in a high-temperature and high-pressure environment, so as to enable the material to obtain ultra-high density. Compared with traditional hot pressing sintering, hot isostatic pressing not only avoids the uneven force on the sample in all directions caused by unidirectional pressure, but also effectively solves the problem that the shape and size of ceramic products are limited to the pressing mold, which helps to expand the method of ceramic preparation and the specification range of ceramic products. Hot isostatic pressing sintering can ensure that the material achieves a uniform density that is almost comparable to the theoretical density, greatly reduces the presence of porosity, and thus significantly optimizes the comprehensive performance of the material. By reducing internal defects and pores, the fatigue properties of the material are effectively improved, and the toughness, ductility and impact strength of the material are greatly improved, so that the product can still maintain excellent stability and durability under extreme conditions; promote the formation of fine-grained and uniformly distributed microstructures of hard materials such as ceramics, and the fine structure enhances the mechanical properties of the material. For powder materials that are difficult to compact by traditional methods, hot isostatic pressing sintering can be used as an efficient and reliable densification method, so that these materials can also reach the ideal state of high density; using hot isostatic pressing sintering, products close to the final shape can be directly manufactured, which greatly reduces the subsequent processing steps and material waste, and improves production efficiency and resource utilization. During the sintering process, the present invention uses a high-purity argon-oxygen mixed gas with an oxygen content of 5%-10%, wherein argon is an inert gas, and its main function is to act as a protective gas to prevent the material in the sintering process from having unnecessary chemical reactions with oxygen or other impurities in the atmosphere, thereby maintaining the purity and quality of the material. At the same time, the use of argon can also help control the atmosphere during the sintering process and avoid other unnecessary chemical reactions. Secondly, the addition of oxygen can intensify the reaction between oxygen and the substance and improve the heat treatment effect. Calcination in an oxygen atmosphere can react with organic matter or impurities in the material to remove impurities and purify the material. In addition, oxygen can react with the material at high temperature to form oxides, thereby improving the thermal stability and oxidation resistance of the material. The addition of oxygen helps to improve the physical and chemical properties of the material.

[0082] Figure 3The dielectric temperature spectrum of the PIN-PYN-PT piezoelectric ceramic material of the present invention is given. The dielectric properties are measured at a frequency of 1kHz using an automatic LCR meter, and the temperature range is 50°C to 450°C. As can be seen from the figure, the theoretical density of the PIN-PYN-PT piezoelectric ceramic is as high as 99.9%, the dielectric constant at room temperature is 3100, and the Curie temperature Tc is 350°C. The piezoelectric coefficient of the PIN-PYN-PT piezoelectric ceramic material of the present invention is measured using a quasi-static d33 instrument, and the piezoelectric coefficient of the PIN-PYN-PT piezoelectric ceramic reaches 720pC / N.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic, characterized in that: The chemical formula of the PIN-PYN-PT solid solution piezoelectric ceramic used is: xPb(In 0.5 Nb 0.5 )-yPb(Yb 0.5 Nb 0.5 )-zPbTiO3, where 0.05≤x≤0.5, 0.2≤y≤0.8, 0.05≤z≤0.

5.

2. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 1, characterized in that: The following steps are involved: PbO, TiO2, precursor InNbO4 powder, and precursor YbNbO4 powder are weighed according to the stoichiometric ratio, wet ball milled and mixed, and directly dried to obtain a mixed material; The obtained mixed material is pre-calcined at 800-1000° C., the pre-calcined product is mixed with ethanol, subjected to secondary dispersion ball milling, and dried and sieved to obtain dry PIN-PYN-PT ceramic powder; Add PVA binder solution to dry PIN-PYN-PT ceramic powder, mix thoroughly and dry to obtain dry powder, press the dry powder into a mold, and heat at 600-700°C for 1-4 hours to remove binder to obtain a ceramic green body; The obtained ceramic green body is sintered by hot isostatic pressing in an oxygen atmosphere at 900-1000° C. and 20 MPa-100 MPa for 1-3 hours to obtain hot isostatically pressed PIN-PYN-PT ceramics; The obtained sample is annealed at 800°C-1000°C for 0.5-2h to obtain ultra-high density PIN-PYN-PT ceramics; The ultra-high density PIN-PYN-PT ceramics were coated with silver electrodes on both sides and then subjected to DC high voltage polarization to obtain PIN-PYN-PT solid solution piezoelectric ceramics.

3. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: The preparation of the precursor InNbO4 powder includes: weighing analytically pure In2O3 and Nb2O5 according to the stoichiometric ratio, mixing by wet ball milling, directly drying, and sintering in a high temperature furnace at 900-1100° C. for 2-6 hours to obtain the precursor InNbO4 powder; The preparation of precursor YbNbO4 powder includes: weighing analytically pure Yb2O3 and Nb2O5 according to the stoichiometric ratio, mixing by wet ball milling, directly drying, and sintering at 950-1050° C. in a high-temperature furnace for 3-8 hours to obtain precursor YbNbO4 powder.

4. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: The amount of PVA adhesive added is 2wt%-10wt%, and the PVA adhesive is a 10% PVA adhesive solution plasticized by glycerin.

5. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: The powder forming method is one of mechanical uniaxial pressing or cold isostatic pressing or a combination of the two methods.

6. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: During hot isostatic pressing sintering, the oxygen atmosphere is formed by a mixture of high-purity argon and oxygen.

7. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: The purity of PbO and TiO2 is analytical grade.

8. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: During DC high voltage polarization: polarization temperature is 120°C, 30 kV / cm polarization electric field is applied, and polarization treatment is performed for 30 minutes.

9. The method for preparing the ultra-high density PIN-PYN-PT solid solution piezoelectric ceramic according to claim 2, characterized in that: The obtained PIN-PYN-PT solid solution piezoelectric ceramics have a theoretical density of up to 99.9% and a quasi-static piezoelectric constant d 33 The highest is 620pC / N, the highest dielectric constant at room temperature is 3100, and the Curie temperature T C The highest temperature is 350℃, the phase transition temperature T rt The maximum is 230℃, the longitudinal coupling coefficient k 33 The highest is 0.57, k t The highest is 0.

57.

10. A transducer piezoelectric device, characterized in that: A PIN-PYN-PT solid solution piezoelectric ceramic prepared by the method according to any one of claims 2 to 9.

Citation Information

Patent Citations

  • Nanostructured dielectric materials for high energy density multilayer ceramic capacitors

    CN104169080A

  • High-temperature piezoelectric ceramic material, preparation method and application

    CN115849905A

  • Piezoceramic material and preparation method thereof

    CN116606143A

  • PYN-PZT-based high-temperature texture piezoelectric ceramic, preparation method and application

    CN118184349A